2005
DOI: 10.1038/sj.bjp.0706300
|View full text |Cite
|
Sign up to set email alerts
|

M2 and M3 muscarinic receptor‐mediated contractions in longitudinal smooth muscle of the ileum studied with receptor knockout mice

Abstract: 1 Isometric contractile responses to carbachol were studied in ileal longitudinal smooth muscle strips from wild-type mice and mice genetically lacking M 2 or M 3 muscarinic receptors, in order to characterize the mechanisms involved in M 2 and M 3 receptor-mediated contractile responses. 2 Single applications of carbachol (0.1-100 mM) produced concentration-dependent contractions in preparations from M 2 -knockout (KO) and M 3 -KO mice, mediated via M 3 and M 2 receptors, respectively, as judged by the sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
98
1
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(118 citation statements)
references
References 35 publications
8
98
1
10
Order By: Relevance
“…Using muscarinic receptor mutant mice, we previously demonstrated that activation of either M 2 or M 3 receptor subtypes produces contraction in intestinal smooth muscle [30]. Moreover, we found that the M 2 -induced contraction largely depends on Ca sensitization as well.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Using muscarinic receptor mutant mice, we previously demonstrated that activation of either M 2 or M 3 receptor subtypes produces contraction in intestinal smooth muscle [30]. Moreover, we found that the M 2 -induced contraction largely depends on Ca sensitization as well.…”
Section: Discussionmentioning
confidence: 99%
“…Rho, via acting on Rho kinase, causes phosphorylation of MLCP to inhibit its activity and thereby induces Ca 2+ sensitization of contractile proteins. Various muscarinic responses of intestinal smooth muscles have been characterized by using muscarinic receptor subtype-KO mice [19,30,31]. Although mRNA for all five muscarinic receptor subtypes (M 1 -M 5 ) has been found in gut smooth muscles [20], only M 2 and M 3 receptors have been shown to mediate muscarinic responses in gut smooth muscles so far.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations